The association of triglyceride-glucose and triglyceride-glucose related indices with the risk of heart disease in a national - Xiaodi Tang; Kexin Zhang; Rong He (Cardiovascular Diabetology)
Abstract Background The association between triglyceride-glucose (TyG), triglyceride-glucose related indices and heart disease remains a topic of debate in the current literature. Existing evidence in Chinese people and in diabetes or non-diabetes patients regarding this association is limited, highlighting the need for further investigation. Methods A cohort study was conducted involving 7945 participants enrolled in the China Health and Retirement Longitudinal Study (CHARLS). The incidence of heart disease was collected by following up 9 years. TyG, TyG with body mass index (BMI), waist circumference (WC), waist-to-height ratio (WHtR) were collected at baseline. Multivariate Cox proportional hazards models, restricted cubic spline (RCS), Kaplan-Meier (KM) curves, subgroup analysis and sensitivity analysis were used to analyze the associations between TyG, TyG related indices and the risk of heart disease in national participants and in type 2 diabetes (T2D) or non-T2D patients respectively. Results During a 9-year follow-up, 1477 participants (18.6%) developed heart disease. Our analysis found a significant positive association between TyG-BMI, TyG-WC, and TyG-WHtR with heart disease risk in all participants. The adjusted hazard ratios (HR) for the highest quartile compared to the lowest were: TyG-BMI 1.73 (95% CI: 1.47–2.03), TyG-WC 1.46 (95% CI: 1.24–1.71), and TyG-WHtR 1.31 (95% CI: 1.11–1.54). However, TyG alone was not significantly associated with heart disease in all participants. In non-diabetic patients, the associations were consistent: TyG-BMI 1.75 (95% CI: 1.47–2.08), TyG-WC 1.47 (95% CI: 1.24–1.75), and TyG-WHtR 1.34 (95% CI: 1.13–1.60). However, in diabetes patients, no significant associations were found between TyG, TyG-WC, TyG-WHtR and heart disease risk except for the highest quartile of TyG-BMI (HR: 1.86, 95% CI: 1.02–3.40). Conclusions In the national population study, higher TyG-BMI, TyG-WC, and TyG-WHtR indices were significantly associated with an increased risk of heart disease, with TyG-BMI and TyG-WC showing stronger correlations. While this association was evident in non-T2D patients, only TyG-BMI was associated with heart disease incidence in T2D patients, underscoring the necessity for further investigation.